SUSTAINABLE PROTECTION OF CHILDREN IN INDONESIA: LESSON LEARNED COVID 19 PANDEMIC - Ai Permanasari (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2023)
The system for protecting children in Indonesia is unsustainable. Violence against children is increasing every year, and has proven to be very high during times of crisis, for example during the COVID-19 pandemic, where cases of violence against children increased by 40 percent. The COVID-19 pandemic has brought into focus many deep-rooted problems and has highlighted the importance of tackling issues facing the most vulnerable children and their families. Children are vulnerable and yet valuable, because the survival of a country's lies in the future of children. It takes a reliable system in every circumstance to protect children, a system that creates a safe and adequate environment for children so that they can grow and develop into their best version. This research is interdisciplinary law research, mainly analyzes the law, and also pays attention to the theory of ecology of child development. This paper used a new paradigm for legal responses that draws from the environmental model, arguing for an ecological approach grounded in the principle of generism. Generism takes as its paramount social values the survival and nurturing of the next generation, hence an “ecogenerist” model. By using the Ecogenerism paradigm, solving child protection problems in a holistic way.